Stress Gastric Ulcers and Cytoprotective Strategies: Perspectives and Trends - Ray, Arunabha; Gulati, Kavita; Henke, Peter (Current Pharmaceutical Design, 2020)
Stress gastric ulceration is a clinical condition leading to morbidity/mortality and complex etiopathological factors are involved. Pharmacotherapy of such gastric mucosal lesions is not consistent and novel strategies are being explored. Targeting gastrointestinal factors have showed equivocal results and there is a possibility of involvement of extra-gastrointestinal factors. Stress is a highly interactive biological response in which the brain plays a key role. The involvement of brain substrates like the limbic system (amygdala, cortex, hippocampus) and behavioral traits has been investigated and research data has shown that the limbic brain-gut axis may be involved in the regulation of gastric mucosal integrity during stressful situations. The amygdaloid complex, its connections with other limbic structures and their neural networks act in tandem to contribute to both stress ulceration and gastroprotection. Complex neurotransmitter interactions in these areas involving biogenic amines and neuropeptides have been shown to modulate stress ulcerogenesis in experimental models. The immune system and brain-immune interactions also appear to play a decisive role in the genesis of such stress gastric lesions and the possibility of a brain-gut-immune axis has been proposed during stress gastric lesions. More recent studies have shown the involvement of oxidative stress and nitric oxide as well as their interactions during such stress gastric pathology, indicating the possible role of antioxidants and NO modulators as gastroprotective agents for stress ulceration. In view of the complex pathophysiology, multiple targets and lack of consistent therapeutic modalities, newer/alternative hypotheses are constantly emerging, which could be explored for effective treatment strategies aimed at gastric cytoprotection. Herbal agents with adaptogenic properties could be worth exploring in this regard as some of these phytopharmaceutical agents used in traditional medicine have been shown to exhibit gastric cytoprotection as part of their anti-stress profile. Further, their interactions with brain neurotransmitters and immune mechanisms and their relative safety could make them prospective leads for stress ulcer prophylaxis and treatment.
Keywords: cytoprotective strategies